A New Condition Number of the Eigenvalue and Its Application in Control Theory (Journal of Computational Mathematics, 1989)
Since the present condition numbers of the eigenvalue are not convenient for control systems design, this paper puts forward a new condition number and indicates its application in designing robust control systems.